Evaluating the Viability of Successive Ring‐Expansions Based on Amino Acid and Hydroxyacid Side‐Chain Insertion. Issue 55 (11th September 2020) - Lawer, Aggie; Epton, Ryan G.; Stephens, Thomas C.; Palate, Kleopas Y.; Lodi, Mahendar; Marotte, Emilie; Lamb, Katie J.; Sangha, Jade K.; Lynam, Jason M.; Unsworth, William P.
Abstract: The outcome of ring‐expansion reactions based on amino/hydroxyacid side‐chain insertion is strongly dependent on ring size. This manuscript, which builds upon our previous work on Successive Ring Expansion (SuRE) methods, details efforts to better define the scope and limitations of these reactions on lactam and β‐ketoester ring systems with respect to ring size and additional functionality. The synthetic results provide clear guidelines as to which substrate classes are more likely to be successful and are supported by computational results, using a density functional theory (DFT) approach. Calculating the relative Gibbs free energies of the three isomeric species that are formed reversibly during ring expansion enables the viability of new synthetic reactions to be correctly predicted in most cases. The new synthetic and computational results are expected to support the design of new lactam‐ and β‐ketoester‐based ring‐expansion reactions. Abstract : Does the ring fit? Ring expansions based on amino/hydroxyacid side‐chain insertion are strongly dependent on ring size. Herein, guidelines are provided on which ring systems are more likely to be successful. Synthetic results are supported by computational chemistry. Calculating the relative Gibbs free energies of isomeric species formed during expansion helps predict the viability of new reactions.